Kebijakan Pembelajaran Jarak Jauh Dalam Perspektif Orang Tua Di Madrasah Ibtidaiyah - Murodah, Nelli (Tasamuh: Jurnal Studi Islam, 2021)
This study is qualitative research that aims to analyze the policy of distance learning in the perspective of parents in madrasah ibtidaiyah. The data was collected with in-depth interviews, participatory observations, and documentation studies. Data analysis using interactive analysis models put forward by Miles and Hubermen. The results showed that parents' perception of the application of distance learning policy in madrasah ibtidaiyah can be said to be different. Some say agree, some disagree, and others disagree. Those who agree say that distance learning is effective, while those who disagree state that distance learning is less effective, not even effective to do.